Impacts of Different Causes on the Inter‐Hemispheric Asymmetry of Ionosphere‐Thermosphere System at Mid‐ and High‐Latitudes: GITM Simulations. Issue 11 (16th November 2021) - Hong, Yu; Deng, Yue; Zhu, Qingyu; Maute, Astrid; Sheng, Cheng; Welling, Daniel; Lopez, Ramon
Abstract: In this study, the Global Ionosphere Thermosphere Model is utilized to investigate the inter‐hemispheric asymmetry in the ionosphere‐thermosphere (I‐T) system at mid‐ and high‐latitudes (|geographic latitude| > 45°) associated with inter‐hemispheric differences in (a) the solar irradiance, (b) geomagnetic field, and (c) magnetospheric forcing under moderate geomagnetic conditions. Specifically, we have quantified the relative significance of the above three causes to the inter‐hemispheric asymmetries in the spatially weighted averaged E‐region electron density, F‐region neutral mass density, and horizontal neutral wind along with the hemispheric‐integrated Joule heating. Further, an asymmetry index defined as the percentage differences of these four quantities between the northern and southern hemispheres (|geographic latitude| > 45°) was calculated. It is found that: (a) The difference of the solar extreme ulutraviolet (EUV) irradiance plays a dominant role in causing inter‐hemispheric asymmetries in the four examined I‐T quantities. Typically, the asymmetry index for the E‐region electron density and integrated Joule heating at solstices with F10.7 = 150 sfu can reach 92.97% and 38.25%, respectively. (b) The asymmetric geomagnetic field can result in a strong daily variation of inter‐hemispheric asymmetries in the F‐region neutral wind and hemispheric‐integrated Joule heating over geographic coordinates. Their amplitude of asymmetry indices can be as large as 20.81% and 42.52%, which can be comparable to the solar EUV irradiance effect. (c) The contributions of the asymmetric magnetospheric forcing, including particle precipitation and ion convection pattern, can cause the asymmetry of integrated Joule heating as significant as 28.43% and 34.72%, respectively, which can be even stronger than other causes when the geomagnetic activity is intense. Plain Language Summary: There are significant differences between the Earth's two hemispheres. Understanding the inter‐hemispheric asymmetries in the mid‐ and high‐latitudes and their impacts on the upper atmosphere is a grand challenge to our geospace community. The main contributions to these asymmetries include: (a) the displacement between Earth's magnetic poles and geographic poles, (b) the seasonal solar EUV irradiation, and (c) the magnetospheric forcing, including the electric field and the auroral particle precipitation. However, it is still unclear to what extent the asymmetries can be generated in the ionosphere‐thermosphere (I‐T) quantities such as the electron density and neutral density between the northern and southern hemispheres due to the above three different causes. In this study, the asymmetric contributions of the above causes on I‐T quantities have been estimated through comparing groups of numerical runs using the Global Ionosphere and Thermosphere Model (GITM). For example, in order to examine the seasonal effects, the GITM runs with the spring equinox, northern summer, and northern winter solstices are compared, keeping the other causes the same. It is found that seasonal dependence of solar extreme ultraviolet irradiance plays a dominant role in causing hemispheric asymmetries in all the examined quantities; our results also suggest that the contribution of the asymmetric magnetospheric forcing could be even more important during intense storms than the other causes shown in this work. Key Points: Solar irradiance in the solstices causes significant asymmetries in the ionosphere‐thermosphere (I‐T) quantities as examined in this study Displacement between the geomagnetic and geographic coordinates produces a diurnal asymmetric variation in the I‐T system Magnetospheric forcing affects the I‐T quantities especially the Joule heating, with stronger precipitation/electric field favoring more heating